Analysis of the Impact of the Merger on Non-Performing Financing and Profitability of Bank Syariah Indonesia (BSI) for the Period 2021 - 2024 - Syarifah Farida; Setiyo Purwanto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the effect of merger policies on the level of Non-Performing Financing (NPF) and profitability at Bank Syariah Indonesia (BSI) during the period 2021 to 2024. Using secondary data from BSI's annual financial statements published by the Financial Services Authority (OJK) and the nonparametric statistical method of the Wilcoxon test, this study tested the significant differences between the NPF conditions before and after the merger. The results of the analysis showed a significant decrease in the NPF ratio from 2.93% in 2021 to 1.90% in 2024, which was followed by an increase in profitability measured through Return on Assets (ROA) and Return on Equity (ROE). This research also highlights the importance of effective risk management and operational efficiency as key factors for the success of mergers in strengthening BSI's position as the largest Islamic bank in Indonesia. These findings provide strategic implications for bank managers and policymakers in optimizing merger synergies to support sharia economic growth and national financial stability.